FUTURE DIRECTIONS OF SPIRITUAL DEVELOPMENT: CREATIVE CONCEPTS AND INITIATIVES - Bozorov Sukhrob Komilovich (Western European Studies, 2025)
This article analyzes the prospects of spiritual transformation processes, their impact on social development, and aspects related to innovative ideas and projects. The study examines the development of moral and spiritual values in the context of globalization and the digital revolution, the significance of new innovative approaches, and the mechanisms for their implementation in society. In addition, the role of reforms being carried out in the spiritual and educational sphere in Uzbekistan, as well as the contribution of modern technologies and social initiatives, is explored
Keywords: Spiritual transformation; innovation; social projects